Kinerja Pegawai Negeri Sipil di Badan Kepegawaian Pendidikan dan Pelatihan Daerah Kabupaten Ponorogo - Ismoyo, Ismoyo (Forum Ilmu Sosial, 2017)
Facing a new paradigm in the field of government, in the areas of management personnel have been issued law number 5 Year 2015 about Staffing Management. Some of the new things that are important and need to get attention, namely: (1) the emphasis of the construction of civil servants based on the system of feats work, competence and professionalism, (2) the professionalism of civil servants which the state apparatus/government should be able to maintain neutrality by separating the country office with the Office of the land, and (3) decentralized local government against staffing authority which is one unified network system bureaucracy in staffing nationwide.Badan Kepegawaian Pendidikan dan Pelatihan (BKPPD) Ponorogo being required to provide professional service and quality since it is closely associated with speed, accuracy, in process and completed the staffing of the affair. Therefore, in carrying out the duties and functions of the entire staff of the BKPPD Ponorogo expected to demonstrate good performance.The purpose of this research is to find out and describe the performance of the apparatur BKPPD. The main data source in the form of the words and actions of the rest is additional data, such as documents, photos, statistics, and other data sources used in this study was the informant/resource person i.e. interview and document/archive. The data collected is reduced in the form of selection and simplification of data and then taken the conclusion as well as evaluate how far the indicator responsiveness, responsibility and accountability to the performance of the apparatur BKPPD. The methods used in this research is descriptive qualitative. The results of this research show that the performance of the apparatus at the BKPPD of Ponorogo categorized better. The study also shows that (1). BKPPD Ponorogo quite responsive to complaints that there are though still there is some weakness (2) level of corporate responsibility BKPPD Ponorogo is quite good, but there are still some flaws (3) accountability of the BKPPD has been very good, which is visible from the work and reporting implemented. Each policy taken accounted for starting from planning to results achieved. In each service already is SOP with standard time period. So there is already a rule that raw about each type of service.The study also gives suggestions about the need for complaints management and service in accordance with standard operational procedures resulting in the granting of service going on harmonious relationships between employees and the recipient BKPPD staffing services.